2019
DOI: 10.1177/0272431619837382
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sibling Victimization and Associations With Self-Perception and Relationship Attachment in Adolescence

Abstract: Research shows that sibling victimization may be as detrimental to adolescent outcomes as peer victimization. However, many questions remain unanswered with regard to protective parenting factors and consequences of sibling victimization among adolescents. This study tested a mediation model in which sibling victimization, predicted by parental monitoring, is associated with parent and peer-adolescent attachment as mediated through adolescent self-perceptions of social competence and self-worth. A three path m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…Other factors can contribute to this. A recent study conducted by Walters et al (2020) intends to explore a mediational model of the effects and consequences of sibling victimization in a sample of 355 adolescents (165 females) with ages ranging between 10 and 15 years. According to the authors, the results indicated a negative association between parental monitoring and sibling victimization in girls.…”
Section: Introduction 1attachment and The Development Of Sibling Viol...mentioning
confidence: 99%
“…Other factors can contribute to this. A recent study conducted by Walters et al (2020) intends to explore a mediational model of the effects and consequences of sibling victimization in a sample of 355 adolescents (165 females) with ages ranging between 10 and 15 years. According to the authors, the results indicated a negative association between parental monitoring and sibling victimization in girls.…”
Section: Introduction 1attachment and The Development Of Sibling Viol...mentioning
confidence: 99%
“…The need to examine the connection between PESV and attachment in adulthood has been noted and implied previously (Meyers, 2016; Perkins et al, 2018). Some studies have specifically examined connections between sibling violence and attachment (Lee et al, 2014; Tibbetts & Scharfe, 2015; Walters et al, 2020), yet these studies focused on youth and young adulthood. Tibbetts and Scharfe (2015) found sibling conflict to be associated with various types of attachment (i.e., secure, fearful, preoccupied, and dismissing) in a sample of undergraduate students.…”
Section: Sibling Violence and Adult Attachmentmentioning
confidence: 99%
“…However, in their models including parental perpetration on dating violence with sibling violence as a mediator, the authors did not test any type of directional associations between attachment anxiety or attachment avoidance and PESV. Similarly, Walters et al (2020) included a sample of youth between 10 and 15 years of age and found sibling victimization to be significantly and negatively correlated with both parental and peer attachment. While insightful regarding the potential impact of PESV on attachment patterns to others in youth and adolescence, this study did not assess attachment in adulthood and whether these patterns last over time.…”
Section: Sibling Violence and Adult Attachmentmentioning
confidence: 99%
“…Tempat dilakukannya penelitian juga bervariasi yakni di italy, brazil, iran, inggris, amerika, swedia, hal tersebut memperkuat hasil survey-survey sebelumnya yang menyatakan bahwa perilaku bullying terjadi hampir disemua negara di dunia serta menjadi masalah di dunia pendidikan secara global. Secara spesifik penelitian mengenai bullying dalam 10 artikel yang direview melakukan penelitiannya di sekolah, meskipun penelitian lain sudah mulai meneliti bullying di berbagai tempat, misalnya di tempat kerja (workplace bullying) (Strandmark, Rahm, Rystedt, Nordström, & Wilde-Larsson, 2018;Fontes, Alarcão, Santana, Pelloso, & de Barros, 2018;Paciello, Fida, Tramontano, Ghezzi, & Barbaranelli, 2019), dan di rumah (sibling bullying) (Dantchev, & Wolke, 2019;Bouchard, Plamondon, & Lachance2018;Walters, Farley, Deater-Deckard, & Kim, 2019).…”
Section: Pembahasanunclassified